Role of surgery in the management of mycetoma foot - Roopavathana S., Beulah; R. N., Abinaya; D. K., Titus; Samarasam, Inian; Thomas, Cecil T.; Chase, Suchita; Nayak, Sukria (International Surgery Journal, 2018)
Background: Mycetoma is a chronic granulomatous infection of skin, subcutaneous tissue and bone caused by either fungi (eumycetoma) or bacteria (actinomycetoma). Here we present our experience in the management of this rare condition. Methods: Patients managed for mycetoma foot from August 2011 to January 2018 in authors’ general surgery department were included. The data was collected retrospectively from the hospitals electronic database. Results: Eight patients were recruited with the mean age of the patient was 52years and had male predominance. Most common clinical presentation was swelling with discharging sinuses in the foot. Imaging performed were X ray foot and MRI. Osteomyelitis was noted in 4 patients (50%). Eumycetoma and actinomycetoma were equal in distribution. Out of 4 patients with eumycetoma, one had grown Acremonium species in the culture and out of 4 actinomycetoma patients, 3 had grown Actinomadura pelletieri and one had Nocardia. Surgical procedures performed were 3 biopsies (37.5%), 3 debridement (37.5%) and 2 amputations (25%). Eumycetoma patients were treated with Itraconazole monotherapy and actinomycetoma patients were treated with Trimethoprim-Sulfamethoxazole and cyclical administration of amikacin. Good response was noted in 6 patients and two patients with Eumycetoma had progression of disease with medical therapy and underwent amputation. Conclusions: High clinical suspicion and tissue for histopathological and microbiological evaluation is mandatory to confirm the diagnosis. Medical therapy plays a major role in the treatment of mycetoma foot even if the bone is involved. Surgical procedures like debridement and amputation are indicated only for failed medical therapy with progression of disease (seen most often with eumycetoma) and if there are secondary bacterial infections.